Estrés laboral y su relación con el desempeño docente en la Institución Educativa N° 60192 9 de octubre nivel primaria, Iquitos 2021-2022 - Jara de la Cruz, Janeth (2023)
The research was carried out to answer the following question: What is the relationship between work stress and teaching performance in the educational institution No. 60192 October 9, primary level Iquitos 2021-2022? and for this purpose the study has formulated as a general objective: Relate work stress and teaching performance in the educational institution subject to the study. The research design was cross-sectional, bivariate, and field with relational research type. The population and sample of the study consisted of 26 teachers, and for data collection questionnaires were applied using the survey technique. The data collection instruments have been validated by experts. Conclusion: The statistical value of Student's t is = 25.311; with p-value (bilateral significance) = 0.000, with a significance level of 5%, which certifies that job stress is related to teaching performance, thus confirming the research hypothesis.